The cycle of earnings inequality: Evidence from Spanish social security data - Stephane Bonhomme; Laura Hospido (Institute for the Study of Labor (IZA), 2012)
We use detailed information on labor earnings and employment from social security records to document the evolution of earnings inequality in Spain from 1988 to 2010. Male earnings inequality was strongly countercyclical: it increased around the 1993 recession, showed a substantial decrease during the 1997-2007 expansion, and then a sharp increase during the recent recession. This evolution was partly driven by the cyclicality of employment and earnings in the lower-middle part of the distribution. We emphasize the importance of the housing boom and subsequent housing bust, and show that demand shocks in the construction sector had large effects on aggregate labor market outcomes.
Keywords: D31; J21; J31; 330; earnings inequality; social security data; unemployment; business cycle; Lohnstruktur; Lohndifferenzierung; Konjunkturelle Arbeitslosigkeit; Spanien